2018
DOI: 10.1136/bmjgh-2017-000702
|View full text |Cite
|
Sign up to set email alerts
|

Costing of three feeding regimens for home-based management of children with uncomplicated severe acute malnutrition from a randomised trial in India

Abstract: Trial designThree feeding regimens—centrally produced ready-to-use therapeutic food, locally produced ready-to-use therapeutic food, and augmented, energy-dense, home-prepared food—were provided in a community setting for children with severe acute malnutrition (SAM) in the age group of 6–59 months in an individually randomised multicentre trial that enrolled 906 children. Foods, counselling, feeding support and treatment for mild illnesses were provided until recovery or 16 weeks.MethodsCosts were estimated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Several studies of community‐based SAM treatment estimate higher cost per patient admitted than we found in Yako. These range from US$56 per child treated in India (Garg et al, 2018) to US$805 in Ghana (Abdul‐Latif et al, 2014). Cost per child recovered varied from US$114 to US$1041 (Chui et al, 2020) compared to our estimate of US$45 under OptiMA and US$60 for those meeting the WHO definition for SAM at admission.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of community‐based SAM treatment estimate higher cost per patient admitted than we found in Yako. These range from US$56 per child treated in India (Garg et al, 2018) to US$805 in Ghana (Abdul‐Latif et al, 2014). Cost per child recovered varied from US$114 to US$1041 (Chui et al, 2020) compared to our estimate of US$45 under OptiMA and US$60 for those meeting the WHO definition for SAM at admission.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty-one percent (19/31) of the studies included at least one country in the African Region (Table 3) [147, 150, 152-155, 157, 158, 160-163, 167, 169, 171-174, 176]. Twenty-three percent (7/31) of studies included countries in the South-East Asian region [148,149,151,156,[164][165][166]. Thirteen percent (4/31) of studies included countries in the East Mediterranean [146,157,168,170], and 6% (2/31) of studies included countries in the American region [159,175].…”
Section: General Study Characteristicsmentioning
confidence: 99%
“…There were nine studies in total identified in this group. Three of them reported on the initiation of treatment within the home for infants and children within the age group of 6 to 59 months [146,156,174] (S4 Table ). One of these three studies was conducted in India, and the costs to the government per child treated ranged from $1,779 to $2,047, depending on the type of RUTF used [156] (Table 6; S4 Table ).…”
Section: Management Of Severe Wasting And/or Bilateral Pitting Oedema...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in India have looked at the cost of services, programs, and conditions,[ 23 , 24 , 25 , 26 , 27 , 28 , 29 ] outpatient and inpatient care at public facilities,[ 30 , 31 , 32 ] and out-of-pocket expenditures (OOPEs) at private facilities. [ 15 , 33 , 34 ] But all these studies pertain to allopathic care.…”
Section: Introductionmentioning
confidence: 99%